Indonesian Female Semiotica Charless Sanders Pierce Instagram Analysis Representation in the Puteri Indonesia Instagram Account : Analisis Semiotika Charless Sanders Pierce Representasi Perempuan Indonesia pada akun Instagram Puteri Indonesia - Ubay, Nisrina Nur; Febriana, Poppy (Indonesian Journal of Innovation Studies, 2023)
This study aims to analyze and a explain representative indonesian women in the Puteri Indonesia instagram account. This research is a qualitative descriptive study using Charles Sanders Pierce's semiotic research method as an analytical tool that is useful for explaining icons, indexes and symbols in uploading photos of the Puteri Indonesia 2020 winners' activities on Puteri Indonesia instagram account. The results of this study state that the representation of Indonesian women in the Puteri Indonesia Instagram account shows that it is in accordance with the criteria that must be owned by a woman who has a selling point. The suitability of the criteria that must be possessed by an Indonesian woman is to have intelligence (brain), attractive personality (behavior), confident and brave (brave) and physical beauty (beauty).